TRAIL induces apoptosis but not necroptosis in colorectal and pancreatic cancer cells preferentially via the TRAIL-R2/DR5 receptor - Nahacka, Zuzana; Svadlenka, Jan; Peterka, Martin; Ksandrova, Marie; Benesova, Simona; Neuzil, Jiri; Andera, Ladislav (Biochimica et biophysica acta. Molecular cell research, 2018)
Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a cytokine that can trigger apoptosis in many types of human cancer cells via engagement of its two pro-apoptotic receptors TRAIL-R1 (DR4) and TRAIL-R2 (DR5). TRAIL can also activate several other signaling pathways such as activation of stress kinases, canonical NF-κB signaling and necroptosis. Though both receptors are ubiquitously expressed, their relative participation in TRAIL-induced signaling is still largely unknown. To analyze TRAIL receptor-specific signaling, we prepared Strep-tagged, trimerized variants of recombinant human TRAIL with high affinity for either DR4 or DR5 receptor. Using these receptor-specific ligands, we examined the contribution of individual pro-apoptotic receptors to TRAIL-induced signaling pathways. We found that in TRAIL-resistant colorectal HT-29 cells but not in pancreatic PANC-1 cancer cells, DISC formation and initial caspase-8 processing proceeds comparably via both DR4- and DR5-activated signaling. TRAIL-induced apoptosis, enhanced by the inhibitor of the Bcl-2 family ABT-737, or by the translation inhibitor homoharringtonine, proceeded in both cell lines predominantly via the DR5 receptor. ShRNA-mediated downregulation of DR4 or DR5 receptors in HT-29 cells also pointed to a stronger contribution of DR5 in TRAIL-induced apoptosis. In contrast to apoptosis, necroptotic signaling was activated similarly by both DR4- or DR5-specific ligands. Activation of auxiliary signaling pathways involving NF-κB or stress kinases proceeded under apoptotic conditions mainly in a DR5-dependent manner, while these signaling pathways were during necroptosis similarly activated by either of these ligands. Our study provides the first systematic insight into DR4-/DR5-specific signaling in colorectal and pancreatic cancer cells.
Keywords: Pancreas; signální transdukce; apoptóza; kolorektální nádory; regulace genové exprese u nádorů; HT29 Cells; Necroptosis; NF-kappa B; Colorectal Neoplasms; Signal Transduction; nádory slinivky břišní; Necrosis; Cell Proliferation; Receptor-specific signaling; TRAIL receptory; TNF-Related Apoptosis-Inducing Ligand; TRAIL; Humans; Gene Expression Regulation, Neoplastic; Pancreatic Neoplasms; Caspase 8; malá interferující RNA; Receptors, TNF-Related Apoptosis-Inducing Ligand; proliferace buněk; kaspasa 8; nekróza; Apoptosis; pankreas; buňky HT-29; RNA, Small Interfering; lidé; protein TRAIL; Cancer